Assessment of the kidney and lung as immune barriers and hematopoietic sites in the invasive apple snail Pomacea canaliculata - Rodríguez, Cristian (2018)
Knowledge on the immune system of Pomacea canaliculata is becoming increasingly important, because of this gastropod's role as intermediate host and vector of Angiostrongylus cantonensis, the etiologic agent of eosinophilic meningitis in humans and domestic animals. Immune defenses of this gastropod comprise both humoral and cellular components, but they may also involve organs that act as immune barriers to prevent the spread of alien molecules and organisms. Both the kidney and lung are here shown to serve this function, because of (1) their positions in blood circulation, (2) the intricate architecture of their blood spaces, and (3) the proliferative and nodulation reactions of hemocytes to an immune challenge. However, these organs differ in that only the kidney shows permanent hemocyte aggregations. Microcirculation in the kidney was found to flow through an intricate vascular bed containing the permanent aggregations, which occurred either as hemocyte islets anchored by cytoplasmic projections of the renal epithelium or as perivascular accretions. Within 96 h of the injection of yeast cells, hemocyte nodules were formed both in the kidney and lung. Moreover, cell proliferation in renal hemocyte islets was measured by bromodeoxyuridine (BrdU) incorporation. The proportion of BrdU positive nuclei increased 48 h after injection. Signs of nodule regression (apoptotic bodies, lipofuscin-like deposits) and a decrease in the proportion of BrdU positive nuclei were found at 96 h. In addition, the area of renal hemocyte islets was significantly increased 96 h after injection. Nevertheless, the high complexity of the small vascular chambers that constitute the lung's respiratory lamina would also facilitate hemocyte-antigen contacts, required to elicit cellular aggregation, and hence, nodulation. To our knowledge, this paper includes the first quantitative indication of hemocyte proliferation after an immune challenge among Caenogastropoda.